Analisis Isi Berita Media Online Radar Bogor terhadap Kepercayaan Pembaca - Eli Yani (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
Online mass media is one of the preferred sources of information because of its speed in conveying information. Despite its advantages, issues have emerged about the lack of credibility of online news due to the news being presented concisely and not providing perspective. Readers do not get actual information because the title and content of the news in the news script presented in online media do not match. This research will analyze the news content presented by the online mass media Radar Bogor to determine the extent to which this media provides news content that is trusted as a source of information using qualitative methods. Radar Bogor media news content analysis will be carried out by selecting 10 news stories published on Radar Bogor's Instagram feed for the period May 2021-June 2021 regarding information on cross-border bans during the Covid-19 pandemic situation. Based on the analysis carried out, news values ​​(characters, closeness, interesting, actual, impact) influence the level of reader trust in the news presented, readers do not like inappropriate headlines and news content.